The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/lt.20870
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for the development of prolonged and severe intrahepatic cholestasis after liver transplantation

Abstract: Predictive factors for intrahepatic cholestasis after orthotopic liver transplantation (OLT) have not yet been established. We sought to identify the incidence and risk factors associated with prolonged severe intrahepatic cholestasis (PSIC) after OLT. We assessed 428 consecutive patients undergoing their first OLT. PSIC was diagnosed if a serum bilirubin concentration was greater than 100 mol/L and/or a 3-fold increase of alkaline phosphatase occurred within the first month after OLT and was sustained for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…Due to improvement in surgical techniques and perioperative care, the incidence of biliary anastomosis strictures and leaks decreased, however the incidence of non-anastomotic bile duct stricture became more apparent [4], [5]. Previous studies in LT have found that apart from the obvious life-saving benefits, an increase in blood loss and subsequent transfusion of blood products has been associated with substantial side effects, such as increased risk of BC [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to improvement in surgical techniques and perioperative care, the incidence of biliary anastomosis strictures and leaks decreased, however the incidence of non-anastomotic bile duct stricture became more apparent [4], [5]. Previous studies in LT have found that apart from the obvious life-saving benefits, an increase in blood loss and subsequent transfusion of blood products has been associated with substantial side effects, such as increased risk of BC [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even in pediatric LDLT, Emond et al (21) reported that cholestasis was more prominent and was prolonged in recipients with smaller LDLT grafts. Although studies evaluating prolonged hyperbilirubinemia in DDLT are limited, Fusai et al (22) reported that functional hyperbilirubinemia >100 lmol/L sustained for at least 1 week after DDLT was associated with poor prognosis. After hepatic resection for tumors, Balzan et al (23) showed that PT <50% and T.Bil >50 lmol/L on POD 5 is associated with a mortality rate exceeding 50% after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in markers of nutritional status such as serum albumin are significant risk factors for both surgical [71] and postsurgical [72] complications of liver transplantation. Moreover, it has been suggested that nonabsorbable disaccharides (such as lactulose) administered for the management of HE may result in intestinal malabsorption in patients with end-stage liver failure with the potential to result in poor transplant outcome [73].…”
Section: Nutrition He and Liver Transplantationmentioning
confidence: 99%